Estimated impact and cost-effectiveness of rotavirus vaccination in Senegal: A country-led analysis. (7th May 2015) - Diop, Abdou; Atherly, Deborah; Faye, Alioune; Lamine Sall, Farba; Clark, Andrew D.; Nadiel, Leon; Yade, Binetou; Ndiaye, Mamadou; Fafa Cissé, Moussa; Ba, Mamadou
Highlights: This cost-effectiveness study was coordinated and performed by a group of technical experts within Senegal. Rotavirus vaccination is projected to be cost-effective from both the provider and societal perspectives under a wide range of input values. Vaccination is expected to lower rotavirus mortality by 42%. Abstract: Introduction: Rotavirus is the leading cause of acute severe diarrhea among children under 5 globally and one of the leading causes of death attributable to diarrhea. Among African children hospitalized with diarrhea, 38% of the cases are due to rotavirus. In Senegal, rotavirus deaths are estimated to represent 5.4% of all deaths among children under 5. Along with the substantial disease burden, there is a growing awareness of the economic burden created by diarrheal disease. This analysis aims to provide policymakers with more consistent and reliable economic evidence to support the decision-making process about the introduction and maintenance of a rotavirus vaccine program. Methods: The study was conducted using the processes and tools first established by the Pan American Health Organization's ProVac Initiative in the Latin American region. TRIVAC version 2.0, an Excel-based model, was used to perform the analysis. The costs and health outcomes were calculated for 20 successive birth cohorts (2014–2033). Model inputs were gathered from local, national, and international sources with the guidance of a Senegalese group of experts including local pediatricians, personnel from the Ministry of Health and the World Health Organization, as well as disease-surveillance and laboratory specialists. Results: The cost per disability-adjusted life-year (DALY) averted, discounted at 3%, is US 92 from the health care provider perspective and US 73 from the societal perspective. For the 20 cohorts, the vaccine is projected to prevent more than 2 million cases of rotavirus and to avert more than 8500 deaths. The proportion of rotavirus deaths averted is estimated to be 42%. For 20 cohorts, the discounted net costs of the program were estimated to be US 17.6 million from the healthcare provider perspective and US 13.8 million from the societal perspective. Conclusion: From both perspectives, introducing the rotavirus vaccine is highly cost-effective compared to no vaccination. The results are consistent with those found in many African countries. The ProVac process and tools contributed to a collaborative, country-led process in Senegal that provides a platform for gathering and reporting evidence for vaccine decision-making.